POTENSI PEMBESARAN IKAN NILA MERAH (Oreochromis sp.) KOLAM AIR DERAS DI DAERAH IRIGASI BANJARAN, PURWOKERTO, JAWA TENGAH - Aris Hidayat (Samakia : Jurnal Ilmu Perikanan, 2018)
Racewaytechnological is a cultivation technology innovation that is able to increase production and productivity. Its development can be done in all areas with large water source discharge and flowing throughout the year, one of which is Banjaran Irrigation. Survey along the irrigation area of Banjaran, Purwokerto with purposive sampling technique is done with the aim to know the potential location of the application of red tilapia fish rearing technology. Land suitability matrics were obtained from the results of field measurements in Cijambe, Subang and Ponggok, Klaten which then performed matching with the results of research and literature supporting the enlargement of tilapia. Giving weight and score is done through approach of index overlay model. Red tilapia rearing atproductive racewaycan be conducted along the irrigation area of Banjaran, Purwokerto. There were 6 locations that can be utilized on one side and 5 locations that can be utilized on both sides.